For Gülden: Activist and intellecual legacies - Elafros, Athena (Feminist Asylum: A Journal of Critical Interventions, 2023)
Panel Honouring the late Dr. Gülden Özcan, University of Lethbridge, Women Scholars’ Speaker Series